2018
DOI: 10.3390/w10050666
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Crop Growth and Water-Saving Irrigation Scenarios for Lettuce: A Monsoon-Climate Case Study in Kampong Chhnang, Cambodia

Abstract: Setting up water-saving irrigation strategies is a major challenge farmers face, in order to adapt to climate change and to improve water-use efficiency in crop productions. Currently, the production of vegetables, such as lettuce, poses a greater challenge in managing effective water irrigation, due to their sensitivity to water shortage. Crop growth models, such as AquaCrop, play an important role in exploring and providing effective irrigation strategies under various environmental conditions. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
0
5
0
1
Order By: Relevance
“…Table 2 presents the basic soil physical properties. Soil texture and bulk density measurement methods have been described in a previous study of Ket et al [55]. Porosity (∅) and void ratio (e) were calculated from bulk density (Bd) assuming an average mineral density of 2.65 g cm −3 [56].…”
Section: Soil Measurementmentioning
confidence: 99%
“…Table 2 presents the basic soil physical properties. Soil texture and bulk density measurement methods have been described in a previous study of Ket et al [55]. Porosity (∅) and void ratio (e) were calculated from bulk density (Bd) assuming an average mineral density of 2.65 g cm −3 [56].…”
Section: Soil Measurementmentioning
confidence: 99%
“…Three studies have addressed this for vegetables (e.g., lettuce, potato) and cereal (e.g., maize) in different parts of the world (e.g., Cambodia, Israel, West Africa). The main objective of Ket et al's (2019) [19] study was to improve the water productivity of lettuce by assessing the impact of multiple water-saving scenarios (full, deficit irrigation) by developing the crop model, AquaCrop, for lettuce (currently not available in catalog) and calibrating it with observations from field experiments for Cambodia. The results suggested that a deficit irrigation strategy can save 20-60% of water compared to full irrigation scenarios.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…AquaCrop is a crop‐water productivity model developed by the Food and Agriculture Organization (FAO) of the United Nations, supporting food security by identifying environmental constraints that affect crop production and crop water productivity (CWP). In Cambodia, the AquaCrop model has been applied to assess climate change impacts on lettuce (Ket et al, 2018) and maize (Na et al, 2017), but has not yet been tested on rice. Previous studies indicate an overestimation of heat sterility in arid environments when using ORYZA2000 model (van Oort et al, 2015).…”
Section: Introductionmentioning
confidence: 99%